Core structures and mobility of ⟨c⟩ dislocations in magnesium. (1st July 2017) - Fan, Haidong; Tang, Jing; Tian, Xiaofeng; Wang, Qingyuan; Tian, Xiaobao; El-Awady, Jaafar A.
Abstract: The core structures and mobility of ⟨c⟩ dislocations in magnesium were predicted using both density functional theory and molecular dynamics simulations. The pure edge and screw cores are compact at 0 K. With increasing temperature up to 700 K, the edge dislocation dissociates into two ⟨c⟩/2 partials on the basal plane, but remains immobile. The screw dislocation remains compact and continuously cross-slips between the three prismatic planes. At room temperature, the screw dislocation only glides after emitting a vacancy at 420 MPa. The Peierls stress of the dislocation after vacancy emission is 50 MPa. Graphical abstract: